Paranoid beliefs and conspiracy mentality are associated with different forms of mistrust: A three-nation study - Martinez, Anton P.; Shevlin, Mark; Valiente, Carmen; Hyland, Philip; Bentall, Richard P. (Frontiers in Psychology, 2022)
Paranoia and conspiracy are terms typically used interchangeably. However, although the underlying content of these types of beliefs might be similar (e.g., seeing others as powerful and threatening), recent research suggests that these constructs differ in important ways. One important feature shared by both constructs is excessive mistrust but this aspect might play different roles in each belief system. In this study we explored the strength of associations of different trust predictors (i.e., trust in institutions, trust in sources of information, perceptual trust, and interpersonal trust) between conspiracy mentality and paranoid beliefs. We tested this association in a large representative multinational sample (UK n=2025; Spain n= 1951; and Ireland n= 1041). Confirmatory factor analysis supported a two-factor model of conspiracy and paranoid beliefs in each nation sample. Path and equality of constraints analysis revealed that paranoia was more strongly associated with perceptual mistrust (bias towards mistrusting unfamiliar faces) whereas conspiracy was more strongly associated with mistrust in political institutions. Although interpersonal mistrust and trust in social sources of information were associated significantly with conspiracy their association with paranoid beliefs was stronger. These findings clarify the role of different trust processes in both belief systems. Limitations of this study are discussed.